2012
DOI: 10.1007/s11999-011-2069-6
|View full text |Cite
|
Sign up to set email alerts
|

Low Incidence of Groin Pain and Early Failure with Large Metal Articulation Total Hip Arthroplasty

Abstract: Background Large-diameter metal-on-metal articulations reportedly improve stability and wear in THAs. However, some reports suggest some patients have unexplained hip and early failures with these implants. Thus, the potential benefits may be offset by these concerns. However, the incidence of these problems is not clearly established. Questions/purposes We therefore assessed hip pain, function, osteolysis, and complications in patients with large-diameter metal-on-metal THA. Patients and Methods We retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 52 publications
(119 reference statements)
2
15
1
Order By: Relevance
“…The total amount of Bimetric/ReCap combinations was high (5464). The short-term survival of Bimetric/ReCap with Magnum bearing surface has been promising also in previous studies (3,21,22). These data support the Australian finding of low short-term revision rate of ReCap THA.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The total amount of Bimetric/ReCap combinations was high (5464). The short-term survival of Bimetric/ReCap with Magnum bearing surface has been promising also in previous studies (3,21,22). These data support the Australian finding of low short-term revision rate of ReCap THA.…”
Section: Discussionsupporting
confidence: 85%
“…Hip resurfacing arthroplasty (HRA) and large-diameter head metal-on-metal total hip arthroplasty (LDH MoM THA) have gained popularity during the last decade in hip surgery (1)(2)(3)(4). Recently, increased numbers of MoM bearing surface wear complications have been detected (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…An increase in wall thickness from 6 mm to 10 mm in MOM components yielded an order-of-magnitude lower shell deformation. Implant factors associated with less wear in MOM articulations and increased survival include surface finish, clearance (affected by head size tolerance, sphericity, and cup deformation), carbon content, and casting process [10]. It is noteworthy that the largest deformation remained less than the smallest radial clearance (0.150 mm) according to the manufacturer's stated tolerances.…”
Section: Discussionmentioning
confidence: 99%
“…Because of these apparent advantages, use of MoM implants increased, and by 2006, they accounted for more than one-third of the US market [9,36]. Although initial reports were satisfactory [5,14,22,28,29], subsequent research demonstrated unacceptable early failure rates of monoblock MoM THAs, resulting in a substantial revision burden [2-4, 6, 7, 10, 12, 13, 15, 18, 19, 21, 24, 25, 27, 30, 32, 33, 36]. These revisions can be complicated by extensive soft tissue and bony defects, persistence of adverse local tissue reaction as well as problems associated with the general need to reduce the head size at the time of revision, perhaps increasing the likelihood of dislocation [1,3,7,10,13,18,19,23,25,31,33].…”
Section: Introductionmentioning
confidence: 99%